EFL Teachers’ Beliefs About Listening and Their Actual Listening Instructional Practices - Mónica Abad (Profile: Issues in Teachers' Professional Development)
This paper reports a mixed-method study on listening instructional practices and beliefs of 50 EFL teachers of public and private universities in Cuenca, Ecuador. The study aimed to provide empirical evidence of listening teaching practices and determine teachers’ beliefs about listening. Data were gathered through a questionnaire and structured class observations. Results evidenced that instructional practices emphasize task completion rather than listening development, are oriented towards the product rather than the process and lack decoding.